Low-Cost Optical Fibre Chemical Sensor for Use in Liquid Acid-Base Titration - Ahmad, Musa; Kaskandar, Mohd. Rosli; Tan, Teng Wong (Universiti Putra Malaysia Press, 2003)
A simple low-cost portable optical fibre chemical sensor instrument has been developed in this study by using a laser diode as a light source and solid-state photodiode as a detector. This inexpensive device is shown to have a good response and can be used in three different liquid acid-base titration studies Le. strong acid-strong base, strong acid-weak base and weak acid-strong base, by using a suitable pH indicator. The results obtained by using this instrument were found comparable with titration data obtained by using conventional pH meter.